2016
DOI: 10.1007/978-1-4939-3628-1_23
|View full text |Cite
|
Sign up to set email alerts
|

The Sponge Implant Model of Angiogenesis

Abstract: The host response observed after the application of an appropriate stimulus, such as mechanical injury or injection of neoplastic or normal tissue implants, has allowed the cataloging of a number of molecules and cells involved in the vascularization of normal repair or neoplastic tissue. Implantation of sponge matrices has been adopted as a model for the accurate quantification of angiogenic and fibrogenic responses, as they may occur during wound healing, in vivo. Such implants are particularly useful becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…A common attempt to repair or replace biological tissues is the implantation of biomedical devices or synthetic matrices. Often, an adverse foreign body reaction occurs in the vicinity of implanted devices [152], associated with inflammatory reactions which can induce vessel growth around the implants [153]. This is a result from persistent inflammatory stimuli, which mediate series of cellular alterations by various surrounding cells.…”
Section: Endothelial Cells and Angiogenesismentioning
confidence: 99%
“…A common attempt to repair or replace biological tissues is the implantation of biomedical devices or synthetic matrices. Often, an adverse foreign body reaction occurs in the vicinity of implanted devices [152], associated with inflammatory reactions which can induce vessel growth around the implants [153]. This is a result from persistent inflammatory stimuli, which mediate series of cellular alterations by various surrounding cells.…”
Section: Endothelial Cells and Angiogenesismentioning
confidence: 99%
“…We hypothesize that this sesquiterpene might modulate the components of the fibrovascular tissue induced by a synthetic matrix of polyether-polyurethane in mice. In this model, inflammatory, angiogenic, and fibrogenic markers can be identified and quantified including cell influx, blood vessel formation, cytokine production, and extracellular matrix deposition. , We found that inflammation and fibrogenesis, but not angiogenesis, in subcutaneous implants were down-regulated by polygodial.…”
mentioning
confidence: 76%
“…In this model, inflammatory, angiogenic, and fibrogenic markers can be identified and quantified including cell influx, blood vessel formation, cytokine production, and extracellular matrix deposition. 18,19 We found that inflammation and fibrogenesis, but not angiogenesis, in subcutaneous implants were down-regulated by polygodial.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Using a well-characterized mouse model of peritonitis, they compared the immuno-pathological responses (e.g. inflammatory cell infiltration, angiogenesis and fibrosis) in three inbred strains (DBA-1, BALB/c, C57BL/6) and one outbred strain (Swiss) [ 47 , 48 ]. These investigators observed highly variable responses among the four different groups of mice at 7 days following implantation.…”
Section: Introductionmentioning
confidence: 99%